Clinical presentation of Mucopolysaccharidosis type II (Hunter syndrome): A Case Report - Rahman, Hafizur; Islam, Md Rafiqul; Rahaman, Hasan Zahidur; Md Ariffujaman, - (Bangladesh Journal of Neuroscience, 2014)
Mucopolysaccharidosis (MPS) is a rare disease, caused by deficiency of lysosomal enzyme. MPS cases have been reported throughout the world. MPS patient typically appear normal at birth, but clinical features appear between two to four years of age. We report a case of 12-years-old boy presented with progressive deformity of multiple joints for eight years duration and gradual decline the cognitive function for the same period. On examination, his head was large, short stature, a coarse facial feature with depressed nasal bridge and stubby finger with flexion of distal interphalangeal joint. There was severe mental retardation. We diagnose the patients as Hunter Syndrome, on the basis of clinical findings, radiological features and positive for MPS screening test in urine. Although the golden standard for diagnosing the type of MPS is enzyme analysis. We could not do enzyme analysis as it is not available in Bangladesh. Bangladesh Journal of Neuroscience 2014; Vol. 30 (1): 53-56